Neutron flux characterization of the Kansas State University TRIGA Mark II’s Northeast Beam Port - Boyington, John Charles (Kansas State University, 2019)
A high-resolution, multi-dimensional flux characterization was performed for the Kansas State University TRIGA Mark II’s Northeast Beam Port for the purpose of informing future experimental work, such as detector characterization, done using the beam. First, the Beam Port geometry was added to the existing reactor model. Then the in-core fission rates were tallied using MCNP to provide a source term for the beam transport. The program ADVANTG was used for automated generation of weight windows to accelerate the convergence of tallies in the beam port model. A tally was then collected at the end of the beam port and results are presented. Results from this tally were used to produce simulated responses and response functions for two detectors: a gold foil-based passive spectrometer and a standard set of Bonner Spheres. An experiment was conducted with both measurement devices to obtain responses. These measurements showed decent shape agreement and a small magnitude bias relative to the simulated results. Finally, the measurements, simulated flux, and response functions were used to unfold a final set of spectra using three different unfolding techniques. The Doroshenko directed divergence and Gravel (modified Sand-II) methods produced physically-realistic spectra which successfully fit the measured data, while MAXED did not.
Keywords: Neutron Spectrometry Beam TRIGA